Ecohydrology of water-controlled ecosystems : soil moisture and plant dynamics - Rodríguez-Iturbe, Ignacio (Cambridge University Press, 2004)
This book addresses the connections between the hydrologic cycle and plant ecosystems. It will appeal to advanced students and researchers from a large range of disciplines, including environmental science, hydrology, ecology, earth science, civil and environmental engineering, agriculture, and atmospheric science.